Kiss the dust - Laird, Elizabeth (London : Macmillan Children's Books, 2007)
Her father's involvement with the Kurdish resistance movement in Iraq forces thirteen-year-old Tara to flee with her family over the border into Iran, where they face an unknown future.
Young Adult.
Young Adult
Keywords: Kurds -- Juvenile fiction; Refugees -- Juvenile fiction; Kurds -- Fiction; Refugees -- Fiction; Kurds -- Fiction; Refugees -- Fiction; Iran -- Juvenile fiction; Iraq -- Juvenile fiction; Iran -- Fiction; Iraq -- Fiction; Iran -- Fiction; Iraq -- Fiction